The Roman army, its role in overcoming the crisis of the century3rd century AD (Journal of the College of Basic Education, 2022)
During the middle of the third century AD, the Roman Empire witnessed a severe crisis at various levels, which plunged it into complete chaos, especially the military, which prompted the emperors to take risks by introducing barbarians into the army, and accordingly the emergence of non-Roman elements in sensitive positions in which they proved their worth, what Finally, they were allowed to assume high positions in the military administration. This research aims to try to shed light on the Roman army and its important role in protecting the borders of the empire from external dangers, and its effective role in averting the crisis of the third century AD, by addressing the structure of the new Roman army and the number of its forces, as well as the various military fortifications taken by the emperors To repel the raids of barbarian raiders.